Coal Seams within Eocene Tanjung Formation of the Barito Basin, Southeast Kalimantan: Sequence Stratigraphic Framework and Geochemical Constraints for Source Potential - Awang H. Satyana; Margaretha Eka M.P.; Moh. Imron (Berita Sedimentologi, 2002)
Significant coal seams intercalate the middle Eocene siliciclastic series of the Lower Tanjung Formation of the Barito Basin, Southeast Kalimantan. The formation can be identified as composed of the seven sequences representing synrift and postrift sediments. The coals occur in the three sequences of the postrift phase with the most regional and the thickest coal seams distribute in the transition between the synrift and postrift phases. The coals were deposited within the environments from paralic to upper deltaic settings in various systems tracts including the late lowstand to early transgressive, late transgressive to early highstand, and early highstand to middle highstand.Geochemical constraints are examined to see the possibility of the coals as sources for oil. The coals have excellent total organic carbon (TOC) of 44-73%, very good hidrogen index (HI) from 285-567 mgHC/gTOC (averagely 425 mgHC/gTOC) and high elemental hydrogen to carbon ratio (H/C) of 0.87 to 1.18 concluding that the coals are liptinitic and can generate oil. These values are much higher than the cut off values established for coal to act as oil source (HI of 200 and H/C of 0.80). Geochemical correlation using carbon isotope and biomarker fingerprinting results in positive correlation meaning that the Tanjung coals have sources the Tanjung oil. The coals may have substantial potential as sources of oil if the coals are volumetrically important.